(untitled) (Research, Society and Development, 2022)
Alopecia X (AX) is a non-inflammatory and non-pruritic skin disease characterized by progressive hair loss. The most commonly affected dogs are male Pomeranian, Chow-Chow and Poodles. Although there is a similarity with endocrinopathies that course with dermatological changes, AX does not bring systemic harm to affected dogs. The diagnosis is based on the exclusion of other diseases that lead to hair loss, in addition to systemic diseases. As it is a disease rarely reported in the literature, the objective of the present work is to make a retrospective study of seven cases of dogs with AX treated in clinical routine, from diagnosis to therapeutic results. At the time, the dogs received a similar therapeutic approach, which consisted of the orchiectomy process, followed by supplementation with omega-3 and vitamin complex. Only one dog was not neutered, due to constant platelet changes. Two dogs underwent the microneedling technique due to partial response to conventional treatment and only one of them showed complete repilation. From the above, it is considered that AX is a disease present in the dermatological routine of dogs and that the recognition of its lesion pattern is important for a better diagnostic and therapeutic direction. In addition, it was observed that, although all the therapies employed resulted in an improvement in hair growth, the therapeutic response was variable, so that some dogs may not show complete repilation. Further researches involving therapy comparison are encouraged in order to provide a better understading of their efficiency.